Peer Education Strategy Through the Utilization of Information Technology Media in Effectiveness of New Normal Policies as An Efforts to Control Covid-19 Pandemic - Sutrisno; Eko Sulistiono; Anajeng Esri Edhi Mahanani (Future Science, 2020)
2020 is a test year for each country globally. The Covid-19 pandemic is a scourge from various sides/fields of life in society, nation, and state. In Indonesia, the impact of the Covid-19 pandemic has been felt in the health, economy, even social and policy sectors. The pandemic, which started at the end of 2019 until now, still leaves homework for various countries, including Indonesia, to immediately carry out countermeasures effectively and efficiently. The policy that will then be taken sees the condition that is still unstable, then leads to WHO recommendations, namely the application of the new normal, including in Indonesia. The policy New Normal which leads to encouraging the implementation of